Patient perceptions of radiographer communication skills in general radiology - Soares, Liliana (2020)
The purpose of this study was to explore of patient perceptions regarding the performance of the Radiographer in terms of interpersonal communication skills and to verify that the professional practice is carried out in accordance with a policy of respect for the Radiographers code of ethics and the charter of patients' rights and duties.